Fractal Morphological Analysis of Bacteriorhodopsin (bR) Layers Deposited onto Indium Tin Oxide (ITO) Electrodes - Vengadesh, P.; Muniandy, S.V.; Abd Majid, Wan Haliza (Elsevier, 2009)
Uniform Bacteriorhodopsin layers for the purpose of fabricating Bacteriorhodopsin-based biosensors were prepared by allowing drying of the layers under a constant electric field. To properly observe and Understand the "electric field effect" on the protein Bacteriorhodopsin, the electric and non-electric field influenced Bacteriorhodopsin layers prepared using a manual syringe-deposition method applied onto Indium Tin Oxide electrodes were structurally investigated using Scanning Electron Microscopy and Atomic Force Microscopy. The results yield obvious morphological differences between the electric and non-electric field assisted Bacteriorhodopsin layers and brings to attention the occurrence of the so-called "coffee-ring" effect in the latter case. We applied stochastic fractal method based on the generalized Cauchy process to describe the morphological features surrounding the void. Fractal dimension is used to characterize the local regularity of the Bacteriorhodopsin clusters and the correlation exponent is used to describe the long-range correlation between the clusters. It is found that the Bacteriorhodopsin protein tends to exhibit with strong spatial correlation in the presence of external electric field compared to in absence of the electric field. Long-range correlation in the morphological feature may be associated to the enhancement of aggregation process of Bacteriorhodopsin protein in the presence of electric field, thereby inhibiting the formation of the so-called "coffee-ring" effect. As such. the observations discussed in this work suggest some amount of control of surface uniformity when forming layers. (C) 2009 Elsevier B.V. All rights reserved.